2018
DOI: 10.1590/1983-40632018v4852122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drought-tolerant corn genotypes by multivariate analysis1

Abstract: The identification of genotypes that are tolerant to water deficit is crucial for the maintenance of the agricultural production. This study aimed to evaluate the genotypic variation for drought tolerance among corn genotypes by means of multivariate analysis, as well as to identify hybrids with high grain yield under conditions of water deficit and full irrigation. For this purpose, an experiment was conducted in a randomized block design, with 36 corn hybrids, being 34 experimental elite and two commercial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The first component was strongly influenced by ear length and number of kernels per ear, while the second component was also influenced by above-ground dry matter, shoot dry matter, and plant height. Some of these traits have already been used successfully in the field, to discriminate corn genotypes in breeding programs aiming at tolerance to drought (Sousa et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The first component was strongly influenced by ear length and number of kernels per ear, while the second component was also influenced by above-ground dry matter, shoot dry matter, and plant height. Some of these traits have already been used successfully in the field, to discriminate corn genotypes in breeding programs aiming at tolerance to drought (Sousa et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that flooding is restrictive to corn plant growth. According to Souza et al (2018), excessive water application can generate hypoxia in the plants, restricting plant matter accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that P. edulis plants are moderately sensitive to water excess in the soil. According to Souza, Bastos, Cardoso and Pereira (2018), excess water supply can lead to hypoxia in plants that restricts biomass accumulation. Under excess water in the soil there are fewer spaces designated to gases and, if it persists, inhibition of respiration, cytosol pH reduction and decreased aquaporin activity is common, according to Taiz and Zeiger (2017).…”
Section: Discussionmentioning
confidence: 99%